Optimisme dan Distres Psikologis pada Perawat Selama Pandemi Covid-19 - Dian Agusti Tanjung; Emil Huriani; Dally Rahman (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2021)
Salah satu dampak psikologis yang ditemui saat pandemi Covid-19 adalah distres psikologis yang dialami tenaga kesehatan khususnya perawat. Distres psikologis memunculkan efek membahayakan bagi individu seperti, tuntutan berlebihan yang menguras energi individu sehingga membuat individu menjadi lebih mudah sakit.Tujuan dari penelitian ini adalah untuk mengetahui hubungan ruang bertugas dan optimisme dengan distres psikologis yang meliputi stres, kecemasan dan depresi pada perawat selama pandemi Covid-19 di RS Paru Provinsi Sumatera Barat tahun 2020. Jenis penelitian ini adalah deskripsi korelatif, dengan populasi 35 perawat. Optimisme diukur dengan kuesioner Life Orientation Test-Revised (LOT-R), stres diukur dengan kuesioner Perceived Stress Scale (PSS-10), kecemasan diukur dengan kuesioner General Anxiety Disorder Scale (GAD-7), dan depresi diukur dengan kuesioner Patient Health Questionnaire (PHQ-9). Hasil penelitian menunjukkan terdapat hubungan yang bermakna antara ruang bertugas dengan distres psikologis yaitu stres, kecemasan dan depresi pada perawat selama pandemi Covid-19 dengan nilai p= 0.003 (stres), p= 0.008 (kecemasan), p= 0.046 (depresi) dengan p<0,05. Serta terdapat hubungan yang bermakna antara optimisme dengan distres psikologis yaitu stres, kecemasan dan depresi pada perawat selama pandemi Covid-19 dengan nilai p= <0,05. Disarankan pada pihak manajemen keperawatan di rumah sakit perlu meningkatkan program manajemen stres bagi tenaga keperawatan, sehingga dapat meminimalisir adanya distres psikologis yang diterima perawat.Kata Kunci: distres psikologis; optimisme; ruang bertugas OPTIMISM AND PSYCHOLOGICAL DISTRESS IN NURSES DURING THE COVID-19 PANDEMIC ABSTRACT The psychological impact that is encountered during the Covid-19 pandemic is the psychological distress experienced by health workers, especially nurse. Psychological distress has harmful effects on the individual who experiences it, such as unpleasant or excessive demands that drain the individual's energy, making it easier for the individual to get sick. The purpose of this study was to determine the relationship between department and optimism with psychological distress including perceived stress, anxiety and depression in nurses and to determine the distress that nurses felt during the Covid-19 pandemic at the Pulmonology Hospital West Sumatera in 2020. The type of study was a descriptive correlative, with a population of 35 nurses. Optimization was measured using the Life Orientation Test-Revised (LOT-R) questionnaire, perceived stress was measured by the Perceived Stress Scale (PSS-10) questionnaire, anxiety was measured using the General Anxiety Disorder Scale (GAD-7) questionnaire, and depression was measured using the Patient Health Questionnaire (PHQ-9). The results showed that there is a significant relationship between department and psychological distress, perceived stress, anxiety and depression in nurses during the Covid-19 pandemic with a value of p <0.05. And there is a significant relationship between optimism and psychological distress, perceived stress, anxiety and depression in nurses during the Covid-19 pandemic. It is suggested that the nursing management at the hospital needs to increase the stress management program for nursing personnel, so that it can minimize the psychological distress received by nurses.Keywords: department; optimism; psychological distress